Accidental Olanzapine Consumption in Children - Kumar, Kalenahalli Jagadish; Samatha, Aleti; Marda, Srikanth; Chaudhary, Divya (Journal of Nepal Paediatric Society, 2018)
Olanzapine is commonly used an atypical antipsychotic drug. Overdose is characterized by agitation, deep coma, blurred vision, myosis, respiratory depression and cardiovascular effects. Cardiovascular toxicity includes alterations in blood pressure, conduction disturbances like prolongation of the QRS/ QT intervals or ventricular dysrhythmias. We report two children with Olanzapine poisoning who presented with altered consciousness and one of them had ECG abnormality. Both of them recovered and discharged.